Measurement of the derivative zw for oscillating wings in cascade - Milne, R. D. (College of Aeronautics, Cranfield, 1955)
Experimental results are reported of the damping derivative zw. for rigid rectangular wings of various aspect ratios in cascades having gap-chord ratios of 2, 1,1/2, 1/3, 1/4. The results show fair agreement with two-dimensional theory. The ranges of Reynolds numbers and frequency parameters were 0.8 to 2.5 x 10) and 0.1 to 0.45 respectively. The results show a strong dependence on Reynolds number which increases with decrease in gap-chord ratio. This effect was eliminated by transition fixation by wires placed at suitable positions down-stream of the wing leading edge.